Implementasi Kebijakan Akademik Tentang Proses Belajar Mengajar (PBM) di Universitas Bojonegoro - Suhindarno, Heny; Setijohadi, Mochtar (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
The purpose of this study was to determine the implementation and factors that support and hinder the implementation of academic policies regarding the teaching and learning process (PBM) at Bojonegoro University. This type of research is descriptive with a qualitative approach. The results of the study indicate that the academic implementation process of the Teaching and Learning Process (PBM) at Bojonegoro University includes: Policy interpretation based on the Rector's Decree of Bojonegoro University, its derivative regulations, human resources, budget, and facilities and infrastructure, policy socialization, policy implementation, and performance achievement. Meanwhile, internal factors that hinder policy implementation include: the absence of technical implementation guidelines, which affect the understanding, attitudes, and behavior of implementers; and external factors are the absence of government regulations that specifically regulate the academic implementation of the Teaching and Learning Process (PBM) at the university level and community participation within the Bojonegoro University environment to support academic activities.